Propuesta de reasentamiento para los habitantes de la comunidad de Cahuají Bajo del cantón Guano - Lema Mayorga, Lady Maribel (2024)
Cahuaji Bajo is a community located in the rural parish of Guanando, within Guano, in an area of volcanic risk. During the eruption of the Tungurahua volcano in 2006, this community was displaced from its original territory. Currently, the population is fragmented, with around 17 families that have returned to their original territory and 38 families that partially live between their old community and “María de los Ángeles” neighborhood of the Guano canton, which causes constant displacement. Due to the parish's geographical location and vulnerability to volcanic threats, a territorial diagnosis was conducted on several scales. At the macro level, the Guano canton has been investigated in general; at the meso level, the populated centers around the parish; and finally, it has been determined that the Cahuaji Bajo community will be unable to return to its former land due to volcanic threats. Resettlement is suggested in the San José de Chazo parish, which has infrastructure, equipment, and a more secure position. Based on the urban analysis and rural conditions, a master plan for San José de Chazo is proposed, which considers the original configuration of the urban fabric and the existing natural edges. Subsequently, an intervention is proposed for the resettlement of Cahuaji Bajo, providing it with equipment that boosts the local economy, especially agricultural practices. The rehabilitation of the three existing ravines that delimit and fragment the territory is proposed, as well as a mobility plan that regulates the distribution of the population towards the expansion polygon. Regarding the architectural project, three types of housing are proposed that are adapted to the needs of the Cahuaji Bajo community resettled in San José de Chazo, considering their agricultural activities and the materials available in the area. This proposal seeks the integration of resettlement with the proposed Master Plan for the existing parish, as well as its relationship with the urban and natural context.